A Nonmetal Plasmonic Z‐Scheme Photocatalyst with UV‐ to NIR‐Driven Photocatalytic Protons Reduction. Issue 18 (6th March 2017) - Zhang, Zhenyi; Huang, Jindou; Fang, Yurui; Zhang, Mingyi; Liu, Kuichao; Dong, Bin
Abstract : Ultrabroad‐spectrum absorption and highly efficient generation of available charge carriers are two essential requirements for promising semiconductor‐based photocatalysts, towards achieving the ultimate goal of solar‐to‐fuel conversion. Here, a fascinating nonmetal plasmonic Z‐scheme photocatalyst with the W18 O49 /g‐C3 N4 heterostructure is reported, which can effectively harvest photon energies spanning from the UV to the nearinfrared region and simultaneously possesses improved charge‐carrier dynamics to boost the generation of long‐lived active electrons for the photocatalytic reduction of protons into H2 . By combining with theoretical simulations, a unique synergistic photocatalysis effect between the semiconductive Z‐scheme charge‐carrier separation and metal‐like localized‐surface‐plasmon‐resonance‐induced "hot electrons" injection process is demonstrated within this binary heterostructure. Abstract : Almost a full‐solar‐spectrum‐driven photocatalytic H2 evolution is achieved over the nonmetal plasmonic Z‐Scheme photocatalyst of the W18 O49 /g‐C3 N4 heterostructure based on the unique synergetic photocatalysis effect between semiconductive Z‐scheme charge‐carriers separation and metal‐like localized‐surface‐plasmon‐resonance.